Software infrastructure and data pipelines established for technical interoperability within a cross-border cooperation for the flora of the Bohemian Forest - Petr Novotný; Stefan Seifert; Martin Rohn; Wolfgang Diewald; Milan Štech; Dagmar Triebel (Biodiversity Data Journal, 2022)
The timely and geographical resolutions, as well as the quantity and taxon concepts of records on the occurrence of plants near national borders is often ambiguous. This is due to the regional focus and different approaches of the contributing national and regional databases and networks of the neighbouring countries. Careful data transformation between national data providers is essential for understanding distribution patterns and its dynamics for organisms in areas along the national borders. Sharing occurrence data through the international data aggregator Global Biodiversity Information Facility (GBIF) is also complicated and has to consider that the underlying taxonomic concept and geographic information system of each single GBIF dataset might be different. In addition, some regional data providers have a restrictive (non-cc) licensing policy which does not allow data publication via the GBIF network. Therefore, it is necessary to investigate new ways to make data fit for use for a better and comprehensive understanding of the Flora of the Bohemian Forest.In this paper, we present a bilateral technical interoperability solution for vascular plant occurrence data for the area between the Czech Republic and Bavaria. We describe the initial state of data providers in both countries and the factual and technical challenges in finding a sustainable concept to establish mutual data sharing. The resulting solution for a functional infrastructure and an agreed data pipeline is described in a step-by-step approach. The new distributed infrastructure allows botanists and other stakeholders from both countries to work within the cross-border context of historical and current plants' distribution.